2006
DOI: 10.1111/j.1365-2929.2006.02548.x
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions about the characteristics of an effective discussion during the reporting phase in problem-based learning

Abstract: To explore student perceptions of factors contributing to the effectiveness of discussions in the reporting phase of the problem-based learning (PBL) process, where students report and synthesise the results of self-study. Forty-eight Year 1 and 2 medical students participated in 6 focus group interviews about the characteristics of effective group discussions and possible improvements. The data were analysed qualitatively in several stages. The analysis yielded 4 main characteristics of effective discussions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
0
40
0
2
Order By: Relevance
“…A small body of qualitative and discourse research on student learning in PBL identified the emergence of students' co-constructed knowledge and their highly interactive dynamics in tutorial groups (for example, Hmelo-Silver and Barrows, 2008;Koschmann et al, 1997;Visschers-Pleijers et al, 2006;Woodward-Kron and Remedios, 2007). For instance, Visschers-Pleijers et al (2006) found that in a PBL setting collaborative knowledge construction among students occurred more frequently than any one student's elaboration of knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small body of qualitative and discourse research on student learning in PBL identified the emergence of students' co-constructed knowledge and their highly interactive dynamics in tutorial groups (for example, Hmelo-Silver and Barrows, 2008;Koschmann et al, 1997;Visschers-Pleijers et al, 2006;Woodward-Kron and Remedios, 2007). For instance, Visschers-Pleijers et al (2006) found that in a PBL setting collaborative knowledge construction among students occurred more frequently than any one student's elaboration of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Visschers-Pleijers et al (2006) found that in a PBL setting collaborative knowledge construction among students occurred more frequently than any one student's elaboration of knowledge. On the other hand, other studies noted several pedagogical issues of learners' participation in PBL, in particular, in non-Western cultural settings (Imafuku, 2012;Khoo, 2003;Legg, 2005; Remedios, Clarke, and Hawthorne, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third mapping phase (M3) reflected how much new information was acquired during private study and applied to the problem. Students were engaged in deep learning (Rendas et al 2006;Visschers-Pleijers et al 2006) by establishing logical relationships amongst the newly acquired facts and concepts and linking them to the knowledge they had before the private study. This phase involved further re-synthesis of information, especially when previously misunderstood concepts needed to be corrected.…”
Section: Discussionmentioning
confidence: 99%
“…La secuencia de los problemas ofrece opciones para que la transferencia de conocimiento intra e inter bloque pueda ser ejercitada 3 . Los beneficios cognitivos del ABP como método de instrucción 4 dependen de la calidad de las interacciones verbales que tienen lugar en los grupos de tutoría 5 , al tiempo que dichas interacciones, de ser socialmente favorables, van estimulando la evolución del grupo hacia un equipo 6 . Este enfoque socio-cognitivo del aprendizaje se enriquece y complejiza si le adicionamos su dimensión cultural.…”
Section: A Facultad De Medicina De La Universidadunclassified